Advances and unmet needs in genetic, basic and clinical science in Alport syndrome: report from the 2015 International Workshop on Alport Syndrome - Gross, O; Kashtan, C; Rheault, M; Flinter, F; Savige, J; Miner, J; Torra, R; Ars, E; Deltas, C; Savva, I; Perin, L; Renieri, A; et al. (Oxford University Press, 2016)
Alport syndrome (AS) is a genetic disease characterized by haematuric glomerulopathy variably associated with hearing loss and anterior lenticonus. It is caused by mutations in the COL4A3, COL4A4 or COL4A5 genes encoding the α3α4α5(IV) collagen heterotrimer. AS is rare, but it accounts for >1% of patients receiving renal replacement therapy. Angiotensin-converting enzyme inhibition slows, but does not stop, the progression to renal failure; therefore, there is an urgent requirement to expand and intensify research towards discovering new therapeutic targets and new therapies. The 2015 International Workshop on Alport Syndrome targeted unmet needs in basic science, genetics and diagnosis, clinical research and current clinical care. In three intensive days, more than 100 international experts including physicians, geneticists, researchers from academia and industry, and patient representatives from all over the world participated in panel discussions and breakout groups. This report summarizes the most important priority areas including (i) understanding the crucial role of podocyte protection and regeneration, (ii) targeting mutations by new molecular techniques for new animal models and potential gene therapy, (iii) creating optimal interaction between nephrologists and geneticists for early diagnosis, (iv) establishing standards for mutation screening and databases, (v) improving widespread accessibility to current standards of clinical care, (vi) improving collaboration with the pharmaceutical/biotech industry to investigate new therapies, (vii) research in hearing loss as a huge unmet need in Alport patients and (viii) the need to evaluate the risk and benefit of novel (including 'repurposing') therapies on an international basis.